Risk factors for coronary artery abnormalities and resistance to immunoglobulin plus ciclosporin A therapy in severe Kawasaki disease: subanalysis of the KAICA trial, randomized trial for cicrosporin A as the first-line treatment - Murayama, Yuri; Hamada, Hiromichi; Shiko, Yuki; Onouchi, Yoshihiro; Kakimoto, Nobuyuki; Ozawa, Yoshihito; Hanaoka, Hideki; Hata, Akira; Suzuki, Hiroyuki (Frontiers in Pediatrics, 2023)
To investigate risk factors for coronary arterial abnormalities (CAAs) and resistance to treatment in patients with Kawasaki disease (KD) receiving intravenous immunoglobulin (IVIG) plus ciclosporin A (CsA) as the first-line treatment, we performed a subanalysis of baseline data of participants in the KAICA trial, a phase 3, randomized study (JMA-ILA00174).All data of the patients enrolled in the KAICA trial, who had a Gunma score ≥ 5 at diagnosis and had been randomly assigned to either IVIG (2 g/kg/24 h) plus CsA (5 mg/kg/day for 5 days) (n=86) or IVIG alone (n=87), were subjected to this study. CAA was defined by a Z score ≥ 2.5 observed within 4 weeks after treatment initiation. Baseline data including genotypes of KD susceptibility genes were compared between subgroups of patients for CAA or treatment response for each treatment group. Backword-forward stepwise logistic regression analyses were performed.Pre-Z-max, defined as the maximum among Z scores on four coronary artery branches before treatment, was higher in patients with CAA in both treatment groups and was associated with CAA in IVIG plus CsA treatment group (odds ratio (OR) = 17.0). High serum total bilirubin level was relevant to treatment resistance only in the IVIG plus CsA group (OR= 2.34).Coronary artery enlargement before treatment is a major determinant of CAA even in KD patients treated with initial IVIG treatment intensified by addition of CsA. Baseline serum total bilirubin level was a risk factor associated with resistance to IVIG plus CsA.